Strategi Pemasaran Digital dengan Smart Green Packaging untuk Meningkatkan Minat Beli Generasi Z Produk UMKM Blitar - Sutanto, Yufi Priyo; Kusuma, Abdi Pandu (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
The purpose of this study is to analyze the influence of digital marketing and sustainable smart packaging on the purchase intention of Generation Z toward MSME products in Blitar City, in order to gain insights into consumer behavior and sustainable business models, particularly among the younger generation. The research employed a mixed-method approach, consisting of quantitative analysis using Partial Least Squares–Structural Equation Modeling (PLS-SEM) on 100 respondents, and qualitative analysis through semi-structured interviews with 10 MSMEs in Blitar City. The findings reveal that digital marketing strategies and smart green packaging exert a positive and significant effect on purchase intention, with a simultaneous contribution of 56%. The variables of smart green packaging and digital marketing strategies individually recorded path coefficients of 0.46 and 0.41, respectively. These results highlight the potential to optimize digital marketing strategies through more interactive social media engagement and environmentally friendly packaging innovations, such as the integration of QR codes and sustainability-based storytelling. Furthermore, this research provides a foundation for formulating a sustainable business model that integrates digital marketing, smart green packaging, and customer experience. Such integration can enhance the branding of MSME products and strengthen their environmentally friendly brand image.